AN ANALYSIS FOR OUTSOURCING BASED RISKS AND PROBLEMS IN LOGISTICS ENTERPRISES - Korucuk, Selçuk; Aytekin, Ahmet; Karamaşa, Çağlar (Journal of process management and new technologies, 2022)
Nowadays businesses transform into the faster, less costly, more flexible, and qualified structure because of developing world economy and fierce competition environment with each passing day. Outsourcing as one of the most essential concepts related to strategic management is considered to meet all the aforementioned conditions. In fact, logistics enterprises composing the main theme of this study tend to the outsourcing like other businesses and prefer it to increase the competitive power and specialized in main area of activity. Despite outsourcing in logistics enterprises provide numerous opportunity and advantage, some risks and problems emerge in case of not achieving the desired accordance and coordination.  In this context risks and problems caused by the outsourcing for enterprises operated in international logistics activities in Giresun province are determined and ranked via the q-rung orthopair fuzzy subjective weighting as one of the multi-criteria decision analysis approaches. According to the results, essential risks and problems caused by the outsourcing for logistics enterprises were found as “Loss of control over the outsourcing firm”, “Inaccurate sales pitches”, “Layoffs” and “Unfulfilled contract provisions” respectively.